Genetic and Genomic Consultation: Are We Ready for Direct-to-Consumer Telegenetics? - Du, Li; Becher, Shmuel I. (Frontiers in Genetics, 2018)
Telegenetics, the applications of telemedicine in the context of genetic services, is a growing market. One of the recent developments in this field is the use of direct-to-consumer (DTC) marketing to promote and advertise genetic and genomic consultant services to consumers. Using Google.com, we identified providers that promote their telegenetics services online. By analyzing their websites, we identify and examine key points regarding DTC telegenetics: how are telegenetics services portrayed, how informed consent is obtained, and what protections are offered to clients’ personal health information? We found that the portrayal of a wide range of telegenetics services on providers’ websites is extremely positive. The risks associated with the implementation of telegenetics were rarely mentioned. The per appointment fees ranged from $179 to $500 USD. Consent forms were often unavailable and did not cover all of the relevant information. The measures for protecting clients’ personal health information by telegenetics providers were found to be generally inadequate and weak. We concluded that DTC telegenetics may increase patients’ access to genetic counseling with affordable costs. But before further developing DTC telegenetics, more research and regulatory improvements are required to guarantee truthful advertising, ensure informed consent, secure personal health data sharing, and warrant adequate privacy protection.